Human Resource Development Based on Spirituality in Islamic Financial Institutions - Nuha, Ulin (UAS PRESS, 2023)
Abstract This article reviews the model of human resource development (HRD) based on spirituality as its main focus within Islamic Financial Institutions, specifically the KSPPS under the Association of Islamic Cooperatives of NU Members (ASKOWANU) in Jepara. The model applied in human resource development incorporates the dimensions of workplace spirituality, which include meaningful work, sense of community, and alignment with organizational values. These three dimensions form the construct variable of spirituality in the workplace. Meaningful work is at the individual level, sense of community is at the group level, while alignment with organizational values is at the organizational level. By implementing these three aspects, companies or organizations will gain not only material but also immaterial and spiritual benefits. The method used in this research is qualitative with a descriptive analysis approach, where the researcher examines the phenomena occurring in the research object. The study concludes that, in general, Islamic financial institutions have already implemented spirituality-based human resource development, but it has not been effective. Therefore, strategic steps are necessary to implement these three aspects operationally within the institution/organization.